2012
DOI: 10.3807/josk.2012.16.3.299
|View full text |Cite
|
Sign up to set email alerts
|

Highly Angle-tolerant Spectral Filter Based on an Etalon Resonator Incorporating a High Index Cavity

Abstract: A high angular tolerance spectral filter was realized incorporating an etalon, which consists of a TiO2 cavity sandwiched between a pair of Ag/Ge mirrors. The effective angle was substantially extended thanks to the cavity's high refractive index. The device was created by embedding a 313-nm thick TiO2 film in 16-nm thick Ag/Ge films through sputtering, with the Ge layer alleviating the roughness and adhesion of the Ag layer. For normal incidence, the observed center wavelength and transmission were ~900 nm an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Given these reasons, thin film devices are investigated as the alternative method. Tae-Hui Noh17 and L. Jay Guo18 demonstrated that the high refractive index material such as TiO 2 and Si 3 N 4 can be employed as the spacing dielectric layer to reduce the dependence of the viewing angle for the Fabry-Perot cavity-based spectral filter. Meanwhile, Mikhail A. Kats proposed a scheme using ultra-thin highly absorbing film on a metallic substrate to produce various colors with a low sensitivity to the incidence angle19.…”
mentioning
confidence: 99%
“…Given these reasons, thin film devices are investigated as the alternative method. Tae-Hui Noh17 and L. Jay Guo18 demonstrated that the high refractive index material such as TiO 2 and Si 3 N 4 can be employed as the spacing dielectric layer to reduce the dependence of the viewing angle for the Fabry-Perot cavity-based spectral filter. Meanwhile, Mikhail A. Kats proposed a scheme using ultra-thin highly absorbing film on a metallic substrate to produce various colors with a low sensitivity to the incidence angle19.…”
mentioning
confidence: 99%
“…As depicted in Figure , the proposed transmission‐type LVF adopts a conventional MDM configuration of Ag‐TiO 2 ‐Ag that is formed on a glass substrate. The top Ag layer is overlaid with an SiO 2 film, which can act as an anti‐reflection coating to improve the transmission efficiency and prevent the Ag from being corroded . The transmission of a Fabry–Perot etalon with an MDM configuration is characterized as T=(1r)2/true(1+r22rcosδtrue), where r is the reflection coefficient of the metal film and δ is the accumulated total phase during a single round‐trip within the cavity.…”
Section: Design Of the Proposed Linear Variable Filtermentioning
confidence: 99%
“…Metal–insulator–metal (MIM) cavitiesa metallic form of the FP cavity , have been widely shown to provide comparable high transmission efficiency narrowband performance, without the requirement for many dielectric layers. MIM-based filters have been proposed for simpler CFA stack architectures; however, as with the all-dielectric approach, each cavity height (spectral band) requires a separate lithographic step. A potential solution to this is to utilize analog lithographic techniques to control FP cavity height.…”
mentioning
confidence: 99%